Numerical simulation of fault development along NE-SW Himalayan profiles in Nepal - Chamlagain, D.; Hayashi, D. (Journal of Nepal Geological Society, 2004)
We examined the state of stress in and around the Himalayan nappes via 2D finite element method using elastic rheology under plane strain condition. This paper describes how we used advanced numerical modelling technique, the finite element method to compute stress and fault as a function of rock layer properties, convergent displacement and boundary condition in the convergent tectonic environment. Interpretation of the calculated results remains somewhat ambiguous because of the limitation of elastic modelling, however, the results are still comparable with geological and geophysical data. Some interesting features of our models are: (1) compressive state of stress in Himalaya; (2) effect of geometry of MHT on stress orientation; (3) the diffuse zone of failure elements along the flat-ramp-flat regions of the Main Himalayan Thrust (MHT); (4) normal and thrust faults pattern in the vicinity of Main Boundary Thrust (MBT) and Main Frontal Thrust (MFT); (5) initiation of faults at depth and their propagation toward south under increasing convergent dis placement, which is consistent with the sequence of thrusting in Himalaya; and (6) direct correlation of simulated fault patterns with geological evidences. Thus overall features of the numerical models are able to conclude that the mid-crustal ramp, MBT and MFT are the most active structures in the present day plate kinematics.